Anti‐infliximab antibody concentrations can guide treatment intensification in patients with Crohn's disease who lose clinical response. Issue 3 (11th December 2017) - Dreesen, E.; Van Stappen, T.; Ballet, V.; Peeters, M.; Compernolle, G.; Tops, S.; Van Steen, K.; Van Assche, G.; Ferrante, M.; Vermeire, S.; Gils, A.
Summary: Background: The presence of antibodies towards infliximab (ATI) is associated with lower infliximab (IFX) trough concentrations and loss of response. IFX treatment intensification is effective for restoring response in most, but not all patients with Crohn's disease (CD). Aim: To compare outcome, pharmacokinetics and immunogenicity of treatment intensification strategies in patients with CD who lost clinical response to IFX. Methods: A retrospective cohort study was conducted, including 103 patients with CD who lost clinical response during IFX maintenance therapy and therefore received a double dose IFX (10 mg/kg) and/or a next infusion after a shortened interval. IFX and ATI concentrations were measured in consecutive trough samples, just before (T0) and after (T+1) treatment intensification. Results: Clinical response (physicians' global assessment) and biological response and remission (CRP) were restored in 63%, 42% and 24% of patients (evaluated at T+1). Treatment intensification increased IFX trough concentrations from 1.2 μg/mL [0.3‐3.6] at T0 to 3.6 μg/mL [0.5‐10.2] at T+1 ( P < .0001). Using a drug tolerant assay, ATI were detected in the T0 sample of 47% of patients. ATI negatively impacted the achieved IFX trough concentration (Spearman r −0.57, P < .0001) and the probability of clinical response ( P = 0.034) at T+1. When ATI were quantifiable but <282 ng/mL eq. at T0, combined interval shortening and dose doubling was more effective for restoring therapeutic IFX trough concentrations (≥3 μg/mL at T+1) than dose doubling alone, which in turn was more effective than interval shortening alone ( P < .001). Conclusion: Antibodies towards infliximab can guide clinical decision‐making on treatment intensification. Abstract : Linked Content This article is linked to Ben‐Horin paper. To view this article visit https://doi.org/10.1111/apt.14489 .